Chert from the Vegamián Formation: A new raw-material supply source in the Cantabrian Mountains (NW Spain) during prehistory. (2016) - Herrero-Alonso, Diego; Tarriño-Vinagre, Antonio; Neira-Campos, Ana; Fuertes-Prieto, Natividad
No abstract available